Introduction to A Theory of the Allocation of Time by Gary Becker - James J. Heckman (Institute for the Study of Labor (IZA), 2014)
Gary Becker's classic study, A Theory of the Allocation of Time, laid the analytical foundations for the study of household production and the allocation of time within the household. The analytical framework of household production theory developed in this paper remained a pillar of his later work on the economics of the family and the economics of nonmarket activities more generally. Becker provided a formal model of households producing outputs like food, children, and housing that bundled goods and time. Becker's great contribution was to apply the model to interpret a broad array of empirical phenomena. Becker's framework allowed for a deeper understanding of the mechanisms of consumer choice, and interpretation of income and substitution effects. Its continuing relevance in empirical economics is a testimony to its power.
Keywords: B31; D13; J24; 330; household production; economics of the family; empirical economics